Dose‐dependent testosterone sensitivity of the steroidal passport and GC‐C‐IRMS analysis in relation to the UGT2B17 deletion polymorphism. Issue 11 (22nd July 2015) - Strahm, Emmanuel; Mullen, Jenny E.; Gårevik, Nina; Ericsson, Magnus; Schulze, Jenny J.; Rane, Anders; Ekström, Lena
Abstract : The newly implemented Steroid Module of the Athlete Biological Passport has improved doping tests for steroids. A biomarker included in this passport is the urinary testosterone glucuronide to epitestosterone glucuronide (T/E) ratio, a ratio greatly affected by a deletion polymorphism in UGT2B17. Suspect urine doping tests are further analyzed with gas chromatography‐combustion‐isotope ratio mass spectrometry (GC‐C‐IRMS) to determine the origin of the androgen. In this study, we investigated the sensitivity of the steroidal module and the IRMS analysis, in subjects administered with three doses of testosterone enanthate (500, 250, and 125 mg), in relation to the UGT2B17 polymorphism. All subjects carrying the UGT2B17 enzyme reached the traditionally used threshold, a T/E ratio of 4, after all three administered doses, whereas none of the subjects devoid of this enzyme reached a T/E of 4. On the other hand, using the athlete biological passport and IRMS analysis, all three doses could be detected to a high degree of sensitivity. The concentrations of all steroids included in the steroidal module were dose dependently increased, except for epitestosterone which decreased independent of dose. The decrease in epitestosterone was significantly associated with circulatory levels of testosterone post dose (rs =0.60 and p=0.007). In conclusion, these results demonstrate that administration of a single dose of 125–500 mg testosterone enanthate could be detected using the athlete biological passport, together with IRMS. Since IRMS is sensitive to testosterone doping independent of UGT2B17 genotype, also very small changes in the steroidal passport should be investigated with IRMS. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The Athlete Biological Passport, together with IRMS, can successfully detect testosterone enanthate injections as small as 125 mg, even in individuals homozygous for the deletion of UGT2B17. However, this sensitivity requires that at least three baseline samples have been collected prior to the doping incidence. Before these baseline samples have been collected, genotyping is an important complementary method.